Detection of Aflatoxigenic Fungi in Dairy Cattle Feed: Findings From Urban Districts of Tigray, Ethiopia - Sisay Weldegebriel Zeweld; Enquebaher Kassaye Tarekegn; Meressa Abraha Welearegay (Veterinary Medicine and Science)
ABSTRACT The growing Ethiopian dairy sector faces significant challenges, including feed contamination by aflatoxigenic fungi, limiting productivity and endangering public health. A cross‐sectional survey was conducted from August to November 2024 to investigate the prevalence of aflatoxigenic fungi in dairy cattle feed sampled from 143 farms across Mekelle, Wukro, Adigrat, Korem and Alamata, as well as the associated risk factors in urban districts of Tigray, Ethiopia. Feed samples, including hay, straw, wheat/maize middling and commercial concentrates, were analysed for fungal contamination using UV light, ammonia vapour tests and colony counts (colony‐forming units per gram [CFU/g]). The analysis revealed that 33.6% of samples contained aflatoxigenic fungi (Aspergillus flavus and Aspergillus parasiticus), whereas 66.4% were contaminated with non‐aflatoxigenic species. Average fungal loads were 2.11 × 105 CFU/g, with dairy farms in Korem town showing the highest contamination (2.495 × 105 CFU/g) and dairy farms in Mekelle city the lowest (1.839 × 105 CFU/g) (F = 125.15, p = 0.001, η2 = 0.784). Feed moisture content (F (1, 135) = 4.041, p = 0.046), environmental conditions (26°C–27°C, >60% humidity) and poor storage practices (F (1, 135) = 223.65, p = 0.001) significantly increased contamination levels. Storage on soil floors led to higher fungal loads (F = 223.65, p = 0.001, η2 = 0.613), whereas owner awareness of aflatoxins reduced contamination (F = 78.27, p = 0.001, η2 = 0.357). The findings highlight the importance of enhancing feed storage practices, providing training to farmers and developing collaborative mitigation strategies. These efforts are crucial for reducing aflatoxin contamination, improving dairy productivity and safeguarding public health.